Dolomitkalk som slaggbildare i LD-konvertern och dess inverkan på fosforreningen - Eriksson, Eva (2012)
At SSAB EMEA in Luleå steel is manufactured mainly based on pellets from LKAB, Malmberget but a small part is from Kiruna. But in the future, the majority of the pellets will come from Kiruna instead of Malmberget. What distinguishes these two kinds of pellets from each other is that the pellet from Kiruna has higher phosphorus content. Coal and coke used in smelting the pellets will also have a higher level of phosphorus. This will contribute that the phosphorus content in pig iron will rise which will make phosphorus removal at SSAB more difficult because the company doesn’t have a practice in dealing with the new amounts of phosphorus. A common knowledge is that a good refining of impurities is to a large part due of the slag. Therefor when it comes to improving dephosphorization there is a proposal to modify the slag slag benefiting removal of phosphor. This can be done by not adding dolomitic lime at LD converter. Dolomitic lime is added today at SSAB to reduce the wear of the LD converter linings composed of MgO. MgO from the linings has a tendency to dissolve in the slag and a method to prevent this is to saturate the slag with MgO by the addition of dolomitic lime. But the adding of dolomitic lime hastens the formation of tricalciumsilikates, 3CaO·SiO2 which inhibits the dissolve of lime. This thesis purpose was to investigate the dolomitic lime effect on dephosphorization by excluding it in the LD process. The goal with this work was to get a clear picture of the dephosphorization without the dolomitic lime and then based from this report develop a praxis for depshosphorization on steel grade that demands low phosphor. At SSAB a computer system is used to calculate a model on how the pig iron should be treated as for example how much lime and dolomitic lime must be added to reach the demands. During this thesis two different trials were done. The first trial in which dolomitic lime was removed from the computer system and the system calculated a model where the ordered requirements were met without ...